Semiallogenic fusions of MSI+tumor cells and activated B cells induce MSI-specific T cell responses - Garbe, Yvette; Klier, Ulrike; Linnebacher, Michael (BMC cancer, 2011)
Various strategies have been developed to transfer tumor-specific antigens into antigen presenting cells in order to induce cytotoxic T cell responses against tumor cells. One approach uses cellular vaccines based on fusions of autologous antigen presenting cells and allogeneic tumor cells. The fusion cells combine antigenicity of the tumor cell with optimal immunostimulatory capacity of the antigen presenting cells.